2019
DOI: 10.3389/fpls.2019.01153
|View full text |Cite
|
Sign up to set email alerts
|

Response of Mustard Microgreens to Different Wavelengths and Durations of UV-A LEDs

Abstract: Ultraviolet A (UV-A) light-emitting diodes (LEDs) could serve as an effective tool for improving the content of health-promoting bioactive compounds in plants in controlled-environment agriculture (CEA) systems. The goal of this study was to investigate the effects of UV-A LEDs at different wavelengths (366, 390, and 402 nm) and durations (10 and 16 h) on the growth and phytochemical contents of mustard microgreens (Brassica juncea L. cv. “Red Lion”), when used as supplemental light to the main LED lighting sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 76 publications
(140 reference statements)
1
27
0
Order By: Relevance
“…In the current study, both experiments showed that the UV-A/Blue and RB light treatments increased levels of phytonutrients, including carotenoids, anthocyanins, and TPC compared to the control. Regarding the UV-A/Blue light, our results are consistent with those of Brazaityte et al [43], who used a similar UV-A light with a peak wavelength of 402 nm and reported high levels of TPC in mustard microgreens.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, both experiments showed that the UV-A/Blue and RB light treatments increased levels of phytonutrients, including carotenoids, anthocyanins, and TPC compared to the control. Regarding the UV-A/Blue light, our results are consistent with those of Brazaityte et al [43], who used a similar UV-A light with a peak wavelength of 402 nm and reported high levels of TPC in mustard microgreens.…”
Section: Discussionsupporting
confidence: 92%
“…In the majority of Brassicaceae species including kale, radish, and broccoli, higher contents of GLs and phenolic bioactive compounds are reported in juvenile stages of plants compared to mature plants [ 1 , 14 , 15 ], where the compounds decrease over time as a result of tissue expansion. The rapid changes in the compounds profiles during germination and early growth of vegetables make early harvesting a particularly relevant factor for maximizing the concentration of these desirable bioactive compounds [ 1 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid changes in the compounds profiles during germination and early growth of vegetables make early harvesting a particularly relevant factor for maximizing the concentration of these desirable bioactive compounds [ 1 , 14 ]. This has contributed to the rising popularity of young vegetables (sprouts and microgreens), as a source of both health-promoting compounds and as functional foods [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Se and Se + UVA treatments had slight negative impact on the total S content in broccoli microgreens ( Figure 7 A), indicating that the metabolic pathway of selenium affected sulfur accumulation. Plants receiving a larger amount of UVA had more intensive mineral uptake in mustard microgreens [ 23 ]. Mineral elements in broccoli microgreens seemed to be unaffected by UVA ( Figure 7 ), indicating that the 15 min irradiation of 40 μmol/m 2 /s UVA was not enough to stimulate mineral uptake in broccoli microgreens.…”
Section: Discussionmentioning
confidence: 99%
“…UVA accounts for 98.7% of the ultraviolet radiation reaching the Earth’s surface [ 16 ] and it is closed to the photosynthetic active spectrum (400 to 700 nm). UVA radiation stimulates phototropins and cryptochromes such as blue light [ 17 ], but it also causes different reactions in plants, which could be useful for improving plant quality without inhibiting growth such as kale [ 18 , 19 ], dropwort [ 20 ], lettuce [ 21 ], sowthistle [ 22 ], and mustard microgreens [ 23 ]. The application of UVA has been particularly effective in enhancing the phytochemicals in plants, but this effect was cultivar- or species-specific.…”
Section: Introductionmentioning
confidence: 99%